High-Performance Normally-Off Al2O3/GaN MOSFET Using a Wet Etching-Based Gate Recess Technique - Wang, Ye; Wang, Maojun; Xie, Bing; Wen, Cheng P.; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Chen, Kevin J.; Shen, Bo (IEEE ELECTRON DEVICE LETTERS, 2013)
This letter reports a normally-OFF Al2O3/GaN gate-recessed MOSFET using a low-damage digital recess technique featuring multiple cycles of plasma oxidation and wet oxide removal process. The wet etching process eliminates the damage induced by plasma bombardment induced in conventional inductively coupled plasma dry etching process so that good surface morphology and high interface quality could be achieved. The fully recessed Al2O3/GaN MOSFET delivers true enhancement-mode operation with a threshold voltage of +1.7 V. The maximum output current density is 528 mA/mm at a positive gate bias of 8 V. A peak field-effect mobility of 251 cm(2)/V.s is obtained, indicating high-quality Al2O3/GaN interface.